Contemporary Perspectives on Ageism - Ayalon, Liat; Tesch-Römer, Clemens (International Perspectives on Aging, 2018)
Older adults outnumbering children; Gerontology/geriatrics; Aging world population; The study of ageism; Ageism is the most prevalent form of discrimination